New axially chiral molecular scaffolds with antibacterial activities against Xanthomonas oryzae pv. oryzae for protection of rice - Chen, Yanlin (2022)
A new class of axially chiral thiazine molecules were constructed and showed promising antibacterial activities against the plant pathogen Xanthomonas oryzae pv. oryzae (Xoo). The axial chiralities of these compounds (R- or S-atropisomer) showed clear impacts on the in vitro inhibitory activities against Xoo. An optimal molecule of this class with the (S)-axially chiral configuration was identified to exhibit inhibitory activity against Xoo with an EC50 value of 4.18 μg/mL. This inhibition efficiency is superior to that of two commercial antibacterial agrochemicals, thiodiazole-copper and bismerthiazol, as the positive controls. This hit compound also performed better than the controls in our in vivo studies. Preliminary mechanistic studies via scanning electron microscopy images showed that our hit compound at a concentration of 10 μg/mL destroyed the bacterial integrity of Xoo. Label-free quantitative proteomics analysis indicated that a total of 366 differentially expressed proteins of the rice plants were significantly influenced in the presence of our hit molecule.